Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
1, \(2x^2+4x=2x\left(x+2\right)\)
2, \(15x^3+5x^2-10x=5x\left(3x^2+x-2\right)=5x\left(x-\dfrac{2}{3}\right)\left(x+1\right)\)
3) \(5x^2\left(x-2y\right)+15x\left(x-2y\right)=\left(5x^2+15x\right)\left(x-2y\right)=5x\left(x+3\right)\left(x-2y\right)\)
4) \(3\left(x-y\right)+5x\left(y-x\right)=\left(x-y\right)\left(3-5x\right)\)
5) \(5x^2-10x=5x\left(x-2\right)\)
6) \(3x-6y=3\left(x-2y\right)\)
7) \(25x^2+5x^3+x^2y=x^2\left(25+5x+y\right)\)
8) \(14x^2y-21xy^2+28x^2y^2=7xy\left(2x-3y+4xy\right)\)
9) \(x\left(y-1\right)-y\left(y-1\right)=\left(x-1\right)\left(y-1\right)\)
10) \(10x\left(x-y\right)-8y\left(y-x\right)=\left(10x+8y\right)\left(x-y\right)=2\left(5x+4y\right)\left(x-y\right)\)
\(1,=2x\left(x+2\right)\\ 2,=5x\left(3x^2+x-2\right)\\ 3,=\left(x-2y\right)\left(5x^2+15x\right)=5x\left(x+3\right)\left(x-2y\right)\\ 4,=\left(x-y\right)\left(3-5x\right)\\ 5,=5x\left(x-2\right)\\ 6,=3\left(x-2y\right)\\ 7,=5x^2\left(5+x+y\right)\\ 8,=7xy\left(2x-3y+4xy\right)\\ 9,=\left(y-1\right)\left(x-y\right)\\ 10,=\left(x-y\right)\left(10x+8y\right)=2\left(5x+4y\right)\left(x-y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: Ta có: \(\left(x+3\right)\left(x+4\right)\left(x+5\right)\left(x+6\right)+1\)
\(=\left(x^2+9x+18\right)\left(x^2+9x+20\right)+1\)
\(=\left(x^2+9x\right)^2+38\left(x^2+9x\right)+360+1\)
\(=\left(x^2+9x\right)^2+2\cdot\left(x^2+9x\right)\cdot19+19^2\)
\(=\left(x^2+9x+19\right)^2\)
b. \(x^2+y^2+2x+2y+2\left(x+1\right)\left(y+1\right)+2\)
\(=\left(x^2+2x+1\right)+2\left(x+1\right)\left(y+1\right)+\left(y^2+2y+1\right)\)
\(=\left(x+1\right)^2+2\left(x+1\right)\left(y+1\right)+\left(y+1\right)^2\)
\(=\left(x+1+y+1\right)^2=\left(x+y+2\right)^2\)
c. \(x^2-2x\left(y+2\right)+y^2+4y+4\)
\(=x^2-2x\left(y+2\right)+\left(y+2\right)^2\)
\(=\left(x-y-2\right)^2\)
d. \(x^2+2x\left(y+1\right)+y^2+2y+1\)
\(=x^2+2x\left(y+1\right)+\left(y+1\right)^2\)
\(=\left(x+y+1\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có y^2+4^x+2y-2^(x+1)+2=0
<=>y^2+2y+1+(2^x)^2-2^x*2+1=0
<=>(y+1)^2 +(2^x-1)^2=0
<=> y+1=0 và 2^x=1
<=> y=-1 và x=0
![](https://rs.olm.vn/images/avt/0.png?1311)
a: Ta có: \(A=x^2-20x+101\)
\(=x^2-20x+100+1\)
\(=\left(x-10\right)^2+1\ge1\forall x\)
Dấu '=' xảy ra khi x=10
![](https://rs.olm.vn/images/avt/0.png?1311)
a: (x-3)(x-1)-x(x-2)=0
=>\(x^2-4x+3-x^2+2x=0\)
=>\(-2x+3=0\)
=>-2x=-3
=>\(x=\dfrac{3}{2}\)
b: \(\left(x+2y\right)^2-\left(2x-y\right)^2\)
\(=\left(x+2y+2x-y\right)\left(x+2y-2x+y\right)\)
\(=\left(3x+y\right)\left(-x+3y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{x+2}{x-3}< 0\)vì \(x+2>x-3\)
\(\left\{{}\begin{matrix}x+2>0\\x-3< 0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x>-2\\x< 3\end{matrix}\right.\)<=> -2 < x < 3
\(\left(x+1\right)\left(x-1\right)=x^2-x+x-1=x^2-1\)
\(\left(x-2y\right)\left(x+2y\right)=x^2+2xy-2xy-4y^2=x^2-4y^2\)
\(\left(x+1\right).\left(x-1\right)\)
\(=x^2-x+x-1\)
\(=x^2+\left(-x+x\right)-1\)
\(=x^2-1.\)
\(\left(x-2y\right).\left(x+2y\right)\)
\(=x^2+2xy-2xy-4y^2\)
\(=x^2+\left(2xy-2xy\right)-4y^2\)
\(=x^2-4y^2.\)
Chúc bạn học tốt!